Prospective Comparison of Diagnostic Accuracy Between Point‐of‐Care and Conventional Ultrasound in a General Diagnostic Department: Implications for Resource‐Limited Settings. (24th March 2017) - Haider, Steffen J.A.; diFlorio‐Alexander, Roberta; Lam, David H.; Cho, Joo Y.; Sohn, Jae Ho; Harris, Robert
Abstract : Objectives: To compare the diagnostic accuracy of hand‐held point‐of‐care (POC) versus conventional sonography in a general diagnostic setting with the intention to inform medical providers or clinicians on the rational use of POC ultrasound in resource limited settings. Methods: Over 3 months in 2010, 47 patients were prospectively enrolled at a single academic center to obtain 54 clinical conventional ultrasound examinations and 54 study‐only POC ultrasound examinations. Indications were 48% abdominal, 26% retroperitoneal, and 24% obstetrical. Nine blinded readers (sonographers, residents, and attending radiologists) sequentially assigned diagnoses to POC and then conventional studies, yielding 476 interpreted study pairs. Diagnostic accuracy was obtained by comparing POC and conventional diagnoses to a reference diagnosis established by the unblinded, senior author. Analysis was stratified by study type, body mass index (BMI), diagnostic confidence, and image quality. Results: The mean diagnostic accuracy of conventional sonography was 84% compared with 74% for POC ( P < .001). This difference was constant regardless of reader, exam type, or BMI. The sensitivity and specificity to detect abnormalities with conventional was 85 and 83%, compared with 75 and 68% for POC. The POC sonography demonstrated greater variability in image quality and diagnostic confidence, and this accounted for lower diagnostic accuracy. When image quality and diagnostic confidence were similar between POC and conventional examinations, there was no difference in accuracy. Conclusions: Point‐of‐care was nearly as accurate as conventional sonography for basic, focused examinations. Observed differences in accuracy were attributed to greater variation in POC image quality.